The Local Community’s Cultural Adaptation to the Influx of Religious Tourists - Ahmad Burhanuddin; Omar Farouk; Muhammad Fazil; Maria Ferreira; Noorhani Dyani Laksmi (Jurnal Lentera Insani, 2026)
This study examines the cultural adaptation of local communities in religious tourism areas in Indonesia as a social process involving adjustment, the negotiation of meaning, identity and economic interests. This study aims to analyse how local communities respond to the development of religious tourism and its impact on sacred values, cultural practices and economic sustainability. This study employs a qualitative approach with a multi-site study design and an interpretative-constructivist perspective. The findings indicate that cultural adaptation proceeds in an ambivalent manner. Religious tourism can open up economic opportunities, broaden social interactions and enhance the visibility of local culture. However, such development can also lead to the commodification of sacred values, changes in ritual practices, inequitable distribution of economic benefits, and tensions between local communities, tourism operators, and managing authorities. These findings emphasise that the sustainability of religious tourism must be assessed not only in terms of growth in visitor numbers or revenue, but also in terms of protecting sacred meanings, ensuring cultural justice, and involving local communities in decision-making. The novelty of this study lies in its emphasis on local communities as active agents in interpreting and negotiating the boundaries between sacred values and commercial interests. Consequently, the governance of religious tourism needs to be more participatory, equitable and sensitive to local cultural values.